History of Steel Beam Design - Galambos, Theodore V. (Engineering Journal, 1977)
This paper is about the history of the design of steel beams. Mainly, it is a brief review of how beams were designed according to the various revisions of the American Institute of Steel Constructions Specification for the Design, Fabrication and Erection of Structural Steel for Buildings since this specification was first adopted on June 1, 1923. The term "beam" as used herein defines structural elements in which axial force is so small as to be negligible. Such beams are relatively long compared to their cross section, and their cross section is made up of plate elements which are relatively thin compared to the depth of the members. Beams are loaded such that they resist the loads, which act transverse to their longitudinal axis, by flexure and shear. Such elements occur in many forms in steel construction, and in any frame they comprise a substantial percentage of all load-carrying members.